‘Other’ cities. The mines as a metaphor of the representation. - Agnello, Fabrizio (DISEGNARECON, 2014)
The study is focused on the representation of a sulphur mine located in the heart of Sicily. The link between the outside plants and the underground network of galleries is intended as a symbol of the overlayed structure of the cities and as a metaphor of the representation. The dualism between apollynian and dyonisiac environments, that is open spaces under the light and underground worlds, where obscurity is permanent, forces the search of proper representation techniques, capable of conveying the peculiarities of each realm. Three plates, drawn in an obsolete way, pencil on art board, try to explicit the complex relations underlying the structure of the mine and the role of the ‘technique’ of representation as an expressive mean, according to Heidegger’s definition. Finally, an analogy between the labyrinth and some trends in contemporary architecture, is proposed.